Satellite microglia show spontaneous electrical activity that is uncorrelated with activity of the attached neuron - Wogram, Emile; Wendt, Stefan; Matyash, Marina; Pivneva, Tatyana; Draguhn, Andreas; Kettenmann, Helmut (European journal of neuroscience, 2016)
Microglia are innate immune cells of the brain. We have studied a subpopulation of microglia, called satellite microglia. This cell type is defined by a close morphological soma-to-soma association with a neuron, indicative of a direct functional interaction. Indeed, ultrastructural analysis revealed closely attached plasma membranes of satellite microglia and neurons. However, we found no apparent morphological specializations of the contact, and biocytin injection into satellite microglia showed no dye-coupling with the apposed neurons or any other cell. Likewise, evoked local field potentials or action potentials and postsynaptic potentials of the associated neuron did not lead to any transmembrane currents or non-capacitive changes in the membrane potential of the satellite microglia in the cortex and hippocampus. Both satellite and non-satellite microglia, however, showed spontaneous transient membrane depolarizations that were not correlated with neuronal activity. These events could be divided into fast-rising and slow-rising depolarizations, which showed different characteristics in satellite and non-satellite microglia. Fast-rising and slow-rising potentials differed with regard to voltage dependence. The frequency of these events was not affected by the application of tetrodotoxin, but the fast-rising event frequency decreased after application of GABA. We conclude that microglia show spontaneous electrical activity that is uncorrelated with the activity of adjacent neurons.
Gesehen am 11.02.2021